2015
DOI: 10.1039/c4dt03866e
|View full text |Cite
|
Sign up to set email alerts
|

Long- and short-range structure studies of KBT-KBZ solid-solutions using synchrotron radiation

Abstract: The relaxor ferroelectric K(0.5)Bi(0.5)TiO(3) has been synthesised in a solid-solution series with K(0.5)Bi(0.5)ZrO(3), as K(0.5)Bi(0.5)Ti1-xZrxO(3). High-resolution synchrotron X-ray powder diffraction and X-ray absorption near edge structure spectroscopy were used to characterise the long-range average and local structural behaviour. Rietveld refinements against diffraction data show that a pseudocubic tetragonal region exists across the whole solid-solution series, with truly cubic symmetry only observed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Interestingly, perovskite-type K 0.5 Bi 0.5 TiO 3 has been shown to undergo a structural transition at approximately 410 °C. 42 The higher structural phase transition temperature in the K 2.5 Bi 2.5 Ti 4 O 13 RP phase can be explained by the difference in composition between the two compounds. On average, the perovskite layer in the RP phase (when calculated using a unit cell from one outer TiO 6 octahedron to another), has 0.625 bismuth atoms per titanium, whereas the perovskite has 0.5 bismuth atoms per titanium.…”
Section: By Plotting the Orthorhombic Distortion ( − 1 B Asupporting
confidence: 54%
See 2 more Smart Citations
“…Interestingly, perovskite-type K 0.5 Bi 0.5 TiO 3 has been shown to undergo a structural transition at approximately 410 °C. 42 The higher structural phase transition temperature in the K 2.5 Bi 2.5 Ti 4 O 13 RP phase can be explained by the difference in composition between the two compounds. On average, the perovskite layer in the RP phase (when calculated using a unit cell from one outer TiO 6 octahedron to another), has 0.625 bismuth atoms per titanium, whereas the perovskite has 0.5 bismuth atoms per titanium.…”
Section: By Plotting the Orthorhombic Distortion ( − 1 B Asupporting
confidence: 54%
“…Charge neutrality is maintained by doping potassium for bismuth on the A site of the perovskite block; i.e., the formula could be better written as K 2 [Bi 2.5 K 0.5 Ti 4 O 13 ]. This is analogous to K/Bi co-occupancy on the perovskite A site of K 0.5 Bi 0.5 TiO 3 ( n = ∞) , and Na/Ca on the A sites of Na 2 Ca 2 Nb 4 O 13 . , Hence, site occupancy was also refined to determine if there was a preferred A site for K/Bi co-occupancy. There are two distinct A sites, as shown in Figure : the two equivalent A sites toward the outer perovskite block closer to the interlayer (A2) and the central/core A site (A1).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…XAFS spectroscopy has also been applied to the study of BNBT’s family, with the aim of studying the effects of substitution of Ti by Zr [108], and the replacement of sodium by potassium [109]. The paper by Blanchard, et al [108] devotes marked interest, again, in the behavior of the Ti K-edge and Zr LIII-edge XANES spectra, focusing on five important photoelectron transitions.…”
Section: X-ray Absorption Fine Structure Spectroscopymentioning
confidence: 99%
“…Bengagi et al attempted to fabricate Zr-substituted BKT [i.e., (Bi 1/2 K 1/2 )-(Zr x Ti 1¹x )O 3 , denoted as BKZT hereafter] ceramics via a conventional solid-state reaction and found that the products included two perovskite phases with different Zr/Ti ratios even after extended thermal annealing as long as 100 h. 18) In another study, Liu et al reported the preparation of single-phase BKZT powders via a solid-state reaction involving a similar long calcination time. 19) However, in their case, a large excess of K 2 CO 3 was added to the samples to compensate for the evaporation of K 2 O during the prolonged calcination. Such a large excess of K makes adjusting the composition of the final product to the stoichiometric composition difficult and may lead to a degradation of the electrical insulation properties of BKZT ceramics, similar to the effect reported for BKT.…”
Section: Introductionmentioning
confidence: 99%